Myeloperoxidase enzyme-catalyzed breakdown of zero-dimension carbon quantum dots - Singh, Pooja; Singh, Lalit Kumar (Frontiers in Medical Technology, 2024)
Carbon quantum dots (CQDs) have shown considerable interest in multiple fields including bioimaging, biosensing, photocatalysis, ion sensing, heavy metal detection, and therapy due to highly tunable photoluminescence and good photostability. Apart from having optical properties CQDs offer several advantages such as low toxicity, environmental friendliness, affordability, and simple synthesis methods. Furthermore, by modifying their surface and functionality, it's possible to precisely control their physical and chemical characteristics. Nevertheless, the growing utilization of carbon-based nanomaterials (CNMs) requires thorough examination of their potential toxicity and long-term impacts on human health and biological systems. In this study, carbon quantum dots (CQDs) were synthesized via a microwave-assisted method using citric acid and urea as precursors, resulting in an average particle diameter of 10.73 nm. The CQDs were further characterized using SEM and FTIR analysis. The CQDs exhibited an excitation wavelength of 320 nm, displaying an emission peak at 430 nm. The enzymatic biodegradation of CQDs by human myeloperoxidase enzyme has been thoroughly investigated here. It is very crucial to understand how these carbon quantum dots interact with the innate immune system that plays a vital role in recognizing and clearing foreign particles. Human myeloperoxidase (MPO), a key enzyme highly expressed in neutrophil granulocytes during inflammatory responses, has been shown to facilitate the biodegradation of carbon quantum dots and various carbon-based nanomaterials through oxidative processes. As a member of the peroxidase family, MPO produces hypochlorous acid (HOCl) and a range of reactive intermediates to eliminate pathogens. Consequently, the study of the biodegradability of CQDs within biological systems is essential for accelerating technological advancements. Here, we have assessed breakdown of CQDs through an oxidative process facilitated by a myeloperoxidase (MPO)-based peroxide system. The human MPO enzyme acted as a catalyst for the CQD degradation, and the addition of hydrogen peroxide (H2O2) and sodium chloride (NaCl) was found to accelerate the reaction.